PELAKSANAAN KEWAJIBAN AYAH DAN UPAYA HUKUM IBU DALAM MEMBERI NAFKAH KEPADA ANAK PASCA PERCERAIAN DI KECAMATAN KAPUAS KABUPATEN SANGGAU - Ananda, Wellanda Umi Fitri; Ma'u, Dahlia Haliah; Ardiansyah, Ardiansyah (Al-Usroh, 2023)
Research aims; 1) Describe the practice of father's obligation to support children after divorce in Kapuas District, Sanggau Regency; 2) Describe the efforts that must be made by mothers so that fathers complete their responsibilities in supporting their children after separation in Kapuas District, Sanggau Regency. In this study, the researcher uses a field research type of research, namely to find out a phenomenon that occurs in the field by seeking as much data as possible and as accurately as possible with the facts that occur. In this appropriate examination technique to decide on the implementation of the father's commitment in providing a living for the child. Data collection methods used by scientists are perception, encounter and documentation. The findings of this study indicate that the implementation of the father's obligations in providing for his child after a divorce occurs in the Kapuas District, Sanggau Regency, varies. Gradually, the arrangement of living by the father was done voluntarily and not implemented. Meanwhile, the legal action that must be taken by the mother so that the father carries out his obligation to bear their children after the separation is that the mother has the right to file an objection regarding the child's maintenance to the Religious Court, if after the decision there is no good faith from the father. So the mother can submit an execution to the Religious Court with a note that the mother knows the financial ability of the ex-husband and what assets the husband has, in order to make it easier for the Court to execute him. In civil law there is no legal consequence that binds the father if he is negligent in providing a child's support, there is only an act of execution in the form of auctioning the goods or property owned by the father to pay for the child's debt. This execution can be carried out at the request of the mother, if there is no submission from the mother, then there is no punishment for the father. But in criminal law, the mother can file a criminal case against child abuse. So that the father can be punished physically, namely in prison. In Law No. 23 of 2004 concerning the Elimination of Domestic Violence, article 9 paragraph (1).